Medicine in the Medieval Islamic World, Innovation and Public Policy and Historical Rulers Perspective - Dr. Muhammad Umar Riaz Abbasi; Dr. Sohail Rasool; Dr. Sehrish Kashan; Dr. Zia Ur Rehman; Dr. Shamaila Athar; Iqra Iftikhar (Al-Qanṭara, 2023)
The field of medicine throughout the Mediaeval Islamic era is a witness to the noteworthy accomplishments of intellectuals, physicians, and policymakers who safeguarded and advanced the medical knowledge inherited from ancient times. This research paper examines the extensive historical background of Islamic medicine in the medieval era, investigating the pioneering advancements achieved by Islamic academics, the influence of governmental policies on healthcare, and the enduring influence on the overall progress of medicine. A comprehensive analysis of the origins of Islamic medical innovation and the corresponding public policies that facilitated its development provides valuable insights into the significant influence of this period on contemporary healthcare methodologies.